Relationships between optimism, social support, self-efficacy, psychological wellbeing and resilience among postgraduate Iranian students in a Malaysian public univesity - Sabouripour, Fatemeh (2015)
International students who are studying as foreign students tend to experience greater stress during their studies. They need to adjust to the new environment and overcome the challenges faced during their studies. Resilience level of these students is an important factor to improve their capability to adjustment to the new environment. International Iranian graduate students studying in UPM is the population of this study. In fact, lack of research on resilience and its related factor among Iranian international students in Malaysia, specifically in UPM, motivated researcher to conduct this research. This study was conducted to examine the relationship between optimism, social support, self-efficacy, psychological well-being, gender and marital status with resilience among Iranian graduate students. To achieve the aims of the study particular objectives were designed as follows: 1) To determine the overall level of resilience among Iranian graduate students in UPM, 2) To investigate significant differences in resilience level across selected demographic variables (gender and marital status) among Iranian graduate students in UPM, 3) To investigate the relationship between optimism, dimensions of social support, self-efficacy and dimensions of psychological well-being with resilience among Iranian graduate students in UPM and 4) To investigate the extent to which dimensions of social support, optimism, self-efficacy and dimensions of psychological well-being significantly predict the level of resilience among Iranian graduate students in UPM. This research is a descriptive correlational study. The 251 of Iranian graduate students of university Putra Malaysia participated in this research. Simple random sampling was employed to collect data. Descriptive and inferential statistical analyses were utilized to address the research objectives. Independent sample t-test was conducted to examine the difference in the resilience level between gender (male and female), marital status (single, married). The relationship between optimism, social support, self-efficacy, psychological well-being and resilience were analysis with Pearson correlation. Besides, a stepwise regression was used to identify significant predictors among optimism, social support, self efficacy, and psychological well-being towards resilience. According to the findings, Iranian graduate students are found to experience high level of resilience. The result of independent t-test indicated that there is no difference in the level of resilience across gender (male and female) and marital status (single and married) among Iranian graduate students. Moreover, the findings of Pearson correlation indicated that there are positive relationships between optimism, three dimensions of social support (support from family, significant others and friends), selfefficacy,and four dimensions of psychological well-being (personal growth, purpose in life, positive relation with others and autonomy) and resilience. Also, the result of stepwise regression analysis revealed that self-efficacy, personal growth, optimism, and purpose in life are significant predictors of resilience. In conclusion, the findings of the study provide practical contributions to the field of educational psychology. This study provides valuable information to lecturers about factors which contribute to resiliency among Iranian graduate students. The findings of this study provide useful implication for the involved parties, such as Ministry of Education Malaysia, educators, counsellors, psychologist, and researchers to improve students’ resilience.